2022
DOI: 10.1109/tvt.2022.3163529
|View full text |Cite
|
Sign up to set email alerts
|

Channel Modeling for Orbital Angular Momentum Based Underwater Wireless Optical Systems

Abstract: The underwater turbulence channel is modelled and a unified statistical distribution is applied for characterizing orbital angular momentum (OAM) propagation in underwater wireless optical communication (UWOC) systems. Based on Monte-Carlo simulations, the effects of turbulences are characterized by the multiple phase screens model considering both the coherence width and scintillation index. The phase screen samples are processed by the randomized spectral sampling discrete Fourier transform (DFT) technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Due to the low capacity and high time delay of traditional underwater communication systems, it is challenging to meet the demand for high-capacity, high-rate underwater communication in industrial and military fields. Underwater wireless optical communication (UWOC), which has the advantages of large bandwidth, high transmission rate and good confidentiality, has attracted the attention of a wide range of researchers [1,2]. Vortex beams, characterized by their possession of orbital angular momentum (OAM), with each photon carrying an OAM value of m 0 ÿ, where unlimited index m 0 represents the topological charge and ÿ is reduced Planck constant, can provide another degree of freedom for multiplexing applications due to the orthogonality among different OAM indexes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low capacity and high time delay of traditional underwater communication systems, it is challenging to meet the demand for high-capacity, high-rate underwater communication in industrial and military fields. Underwater wireless optical communication (UWOC), which has the advantages of large bandwidth, high transmission rate and good confidentiality, has attracted the attention of a wide range of researchers [1,2]. Vortex beams, characterized by their possession of orbital angular momentum (OAM), with each photon carrying an OAM value of m 0 ÿ, where unlimited index m 0 represents the topological charge and ÿ is reduced Planck constant, can provide another degree of freedom for multiplexing applications due to the orthogonality among different OAM indexes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Underwater wireless optical communication (UWOC) has received extensive attention from researchers due to the benefits of high transmission rate and good confidentiality compared to traditional underwater communication methods [1]. In recent years, the application of multiplexing techniques such as orthogonal frequency division multiplexing and optical code division multiple access, etc has contributed to the rapid development of high-capacity free space optical communications [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the unified statistical studies, turbulent channel models were examined based on both experimental and simulation data by using lognormal, gamma-gamma, generalized gamma, Weibull, exponentiated Weibull and K distributions, and results were obtained in the presence of variations in temperature, salinity and air bubbles [26]- [30]. In [26], the validity of statistical distributions was evaluated by using experimental results for weak to strong turbulence regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a dual-hop UWOC system operating in underwater medium (both outage probability and average BER) was analyzed for exponentialgeneralized Gamma distributed channel model in the presence of air bubbles and temperature gradients and it was shown that dual-hop UWOC system has potential to mitigate the turbulence effect [29]. The impact of spatial diversity techniques for orbital angular momentum (OAM) beams was investigated in [30] and significant improvement in the average channel capacity, BER and outage probability was reported. The unified statistical method related studies for optical wireless communication was also performed for adaptive optics that remains an important tool in terms of mitigating the turbulence effect [31], [32].…”
Section: Introductionmentioning
confidence: 99%